Normalisasi Hubungan Diplomatik Uni Emirat Arab – Israel: Analisis Rasionalitas Kebijakan Politik Luar Negeri Uni Emirat Arab - Ahmadi, Sidiq; Bumi, Jasmine Armantyas Safannah (POLITEA, 2022)
The foreign policy of the United Arab Emirates (UAE) to normalize relations with Israel in 2020 has caused controversy and sparked widespread criticism, especially from Muslim countries, because it is considered to have violated the 2002 Arab Peace Initiative agreement and betrayed a commitment to support Palestine. This article is aimed to analyze the rationality of the UAE's decision mentioned above. This is qualitative research with library research methods. The analysis was carried out using the Rational Actor Model from Graham T Allison. This research found that the decision of the United Arab Emirates to normalize relations with Israel is rational. This option is calculatedly the most beneficial for achieving the United Arab Emirates' national interests, namely, increasing its defense and security sector from Iranian threats, maintaining economic stability, and strengthening its position in the international system.